Burden of itch in ichthyosis: a multicentre study in 94 patients. (6th May 2019) - De Palma, A.M.; Mazereeuw‐Hautier, J.; Giehl, K.; Hernández‐Martin, A.; Merlos, M.; Moons, P.; Morren, M.A.
Abstract: Background: From clinical experience, we know that itch is a major concern for many ichthyosis patients. Nonetheless, no previous studies specifically addressed the issue of itch in ichthyosis. Objective: The objective of this study was to specifically address the burden of itch and all its dimensions in ichthyosis patients. Methods: Ninety‐four ichthyosis patients from four different centres were recruited to participate in this cross‐sectional, questionnaire‐based study. All participants completed the Leuven Itch Scale, a multidimensional self‐report instrument that quantifies the frequency, duration, severity, distress, consequences and surface area of itch. Results: Participants included 18 keratinopathic types, 55 autosomal recessive congenital ichthyoses, 11 X‐linked recessive ichthyoses (XLRIs), 6 Netherton's ichthyoses, 1 Sjögren–Larsson type, 1 Iocrin ichthyosis and 2 unknown subtypes. Itch occurred in 93% of all patients. In patients with itch, 63% reported that it was often or always present, although most itch episodes were short in duration. Itch, in all its dimensions, was worst in patients with Netherton syndrome. Patients with XLRI had in general a lower itch profile. About half of all ichthyosis patients reported to experience flares during a change in weather, in a hot environment or in stressful situations, whereas a cold environment led to itch in only 26% of patients. The most significant consequences of itching were lesions from scratching, difficulties in falling asleep, bad mood and loss of concentration. Conclusions: Itch is a major concern in patients with ichthyosis, with significant impact on daily life. Research on future treatments should therefore take itch into consideration and itch should be evaluated in clinical studies. Among the studied subgroups, Netherton patients experienced the most severe consequences.